Proliferation and Contributions of National Database Studies in Otolaryngology Literature Published in the United States: 2005-2016. (September 2018) - Subbarayan, Rahul S; Koester, Lindsey; Villwock, Mark R; Villwock, Jennifer
Objective: Health registries and discharge-level databases are powerful tools. Commonly used data sets include the Nationwide Inpatient Sample (NIS); Surveillance, Epidemiology, and End Results Program (SEER); National Cancer Database (NCDB); and American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP). This study investigated the frequency with which these resources are being used and categorized their contributions to literature. Design: A literature review from 2005 to 2016 for papers utilizing the aforementioned databases and publishing in The Laryngoscope, JAMA-Otolaryngology, Head and Neck, Otolaryngology-Head and Neck Surgery, and International Forum of Allergy and Rhinology was conducted. Results were categorized based on the contribution(s) of the paper. The incidence rate of database publications was calculated for each year along with the 95% confidence intervals using a Poisson distribution. Results: Three hundred ten studies were identified. Seventy percent report descriptive findings, and 65% report outcomes/survival. Approximately 18% made clinical recommendations. In 2005, the incidence rate of database publications was 3 per 1000 journal publications (95% CI, 1-9) and remained relatively stable until 2008. From 2010 onward, there was a persistent increase in publications, culminating in the highest incidence rate in 2016 of 26 database publications per 1000 journal publications (95% CI, 20-32). Conclusions: There was a nearly 10-fold increase in database publications in 2016 compared to 2005. The majority provide descriptive data and outcomes measures. The role of these studies warrants further investigation.